PECULIARITIES OF PERFORMING TECHNIQUES OF THE 20TH CENTURY FEMALE CLASSICAL DANCE - CASIAN, TATIANA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică)
This article is devoted to the problem of performing techniques of the 20th century female classical dance using examples of outstanding dancers such as A. Pavlova, M. Fonteyn, M. Plisetskaya, N. Pavlova,.S. Guillem. The emphasis was placed on identifying and describing the specific performance technique of each dancer in general and the creation of an artistic image in particular. At the same time, an attempt was made to identify the main, dominant features of the performance technique of each of the named dancers. The second part of the article is devoted to a comparative analysis of the performing technique of female classical dance of famous dancers and, on this basis, to determine what changes occurred in the performing technique over a certain historical period. In this context, special attention is paid to various choreographic schools, which differ in many ways, including in relation to the performance technique of classical dance. In conclusion, it is stated that the development of female performance technique of classical dance continues in the 21st century.